The Management of Communication Skills and Its Relationship to the Quality of Teaching Among College Members at the College of Physical Education and Sports Sciences, University of Samarra - Mohammed, Azzam Makki; Abdulmaged, Mustafa Ahmed; Younus, Ali Ayoub (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2025)
This study aims to identify the management of communication skills and the quality of teaching among the College members of the College of Physical Education and Sports Sciences, and to identify the relationship between the management of communication skills and the quality of teaching for College members as well. Researchers have adopted a descriptive methodology with a correlational survey method, based on the nature of this research. The research community and sample consisted of the entire number of College members of the College of Physical Education and Sports Sciences, University of Samarra (46). The approach was a full population (census) count. According to Data Analytics, the researchers used multiple statistical tools to obtain results that serve the objectives of the research. The research sample was characterized by effective management of communication skills and a high degree of teaching quality. The study also concluded that there is a positive correlational relationship between the management of communication skills and the quality of teaching among College members in the College of Physical Education and Sports Sciences at the University of Samarra.